A new earthquake model may explain discrepancies in San Andreas fault slip. Issue 35 (2nd September 2014) - Schultz, Colin
<x xml:space="preserve">Abstract</x> Investigating the earthquake hazards of the San Andreas fault system requires an accurate understanding of accumulating stresses and the history of past earthquakes. Faults tend to go through an "earthquake cycle"—locking and accumulating stress, rupturing in an earthquake, and locking again in a well‐accepted process known as "elastic rebound." One of the key factors in preparing for California's next "big one" is estimating the fault slip rate, the speed at which one side of the San Andreas fault is moving past the other.